ChangeSUB: A power efficient multiple network-on-chip architecture. (May 2020) - Baharloo, Mohammad; Aligholipour, Rashid; Abdollahi, Meisam; Khonsari, Ahmad
Abstract: Applying power gating on network-on-chip (NoC) as an effective static power-aware technique could lead to a significant reduction in on-chip network performance. Since the NoC performance has a considerable impact on the overall chip performance, providing a trade-off between chip power and its performance is crucial. To this end, applying power gating in multiple network-on-chip (multi-NoC) instead of traditional NoC is a promising solution. However, in multi-NoC, waking-up a chain of routers in a switched-off sub-network (subnet) incurs performance penalty. In this paper, we introduce an architecture, namely ChangeSUB, which provides an opportunity to change the subnet of packets in multi-NoC architecture. In the proposed architecture, packets avoid encountering switched-off routers by changing their subnet. Experimental results indicate that compared to traditional multi-NoC design, the proposed architecture decreases the network latency, execution time, and NoC's static power consumption by 10.5%, 4.5%, and 17.6%, respectively, with just imposing 1.9% hardware overhead.